Estructura y tipos de créditos de la Banca Múltiple en el Perú - Cortez Cortez, Gaby (2012)
The structure and types of credit of Commercial Banks in Peru, is the result of the strategies and the dominant position held by some banks in the system to diversify its financial operations, and serve customers with a strong presence in various sectors of the economy, leaving spaces to other banks that have less economic power and operational capability for the development of its activities.